Preparation, characterization and antiglycation activities of the novel polysaccharides from Boletus snicus - Liping, Sun; Xuejiao, Su; Yongliang, Zhuang (International journal of biological macromolecules, 2016)
Boletus snicus (BS) is one of the commercially important mushroom species. Two polysaccharides (BSP-1b and BSP-2b) were extracted and purified from the body of BS by DEAE-cellulose and Sephadex G-100 column chromatography. The average of molecular weight of BSP-1b and BSP-2b were 59.21kDa and 128.74kDa. BSP-1b is a heteropolysaccharide with a large number of glucose and a small amount of mannose, glucosamine hydrochloride and arabinose. The monosaccharide compositions of BSP-2b contain mannose, glucuronic acid, glucosamine hydrochloride, glucose, galactose, arabinose with the molar ratio of 10.70:6.95:12.05:12.57:1.83:1.00. The FTIR spectra and NMR analysis demonstrated that BSP-1b and BSP-2b existed pyranose ring structure and BSP-2b had high content of uronic acid. The antiglycation activities of BSP-1b and BSP-2b were investigated. The results showed BSP-1b and BSP-2b had high inhibitory effects on glycation and exhibited dose-dependent responses. BSP-2b showed stronger antiglycation activity than BSP-1b. This study indicated that the BSP-2b could effectively inhibit the formation of advanced glycation end-products.